PUSAT STUDI JEPANG DI BANJARBARU - Muhammad Nor Erfansyah; Akbar Rahman (JURNAL TUGAS AKHIR MAHASISWA LANTING, 2025)
The Japanese Study Center is a place for learning, introduction and culture from Japan, located in Banjarbaru, South Kalimantan. A Study Center which can be a place to learn about language, writing, behavior and culture in Japan and as a place to attract interest from people who are interested in getting to know Japanese culture as well as a place to prepare basic knowledge for those who wish to go to Japan. This Japanese Study Center uses concepts from Japanese architecture which are applied to the design of the outer and inner spaces of buildings so that they can bring out the nuances of Japanese architecture itself. The problems that exist at the Japanese Study Center will be answered through the concept of "Wabi Sabi, Kanso and Engawa" which is applied to the design of interior and exterior spaces which aims to present a nuance of Japanese architecture through garden and interior design in buildings.